Effect of myoinositol plus metformin versus metformin alone on high serum AMH level in infertile PCOS women: clinical and biochemical response - Islam, Munmun; Sirazi, Abu Shaleh M. Mohiuddin; Alam, Humaira; Rolly, Suraiya Jahan; Sultana, Rebeka; Al Tarique, Mostafa M.; Mahmud, Khan Shihan; Banu, Jesmine (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Polycystic ovary syndrome (PCOS), a common endocrine disorder in reproductive-age women, is characterized by insulin resistance, hyperandrogenism, and elevated serum AMH levels. Both metformin and myoinositol improve insulin sensitivity through different mechanisms, potentially enhancing reproductive outcomes. This study aimed to compare the clinical and biochemical effects of combined myoinositol and metformin therapy versus metformin alone in reducing high serum AMH levels in infertile PCOS women. Methods: This randomized controlled trial at BSMMU’s department of reproductive endocrinology and infertility (July 2022-June 2023) randomized 80 PCOS women (18-35 years) to myoinositol+metformin (n=40) or metformin alone (n=40) for 3 months. We assessed AMH (primary outcome), BMI, waist-hip ratio, menstrual regularity, hormones (LH/testosterone), glucose metabolism, and pregnancy rates, analyzed via SPSS 23 (t-tests; p<0.05 significant). Results: In 80 subfertile PCOS women (40/group), myoinositol+metformin (group A) outperformed metformin alone (group B): greater reductions in BMI (27.1 to 24.5 versus 27.4 to 25.3), waist-hip ratio (0.91 to 0.86 versus 0.90 to 0.88), AMH (12.2 to 9.5 versus 12.3 to 8.6 ng/ml), LH (10.1 to 6.4 versus 9.9 to 6.9 mIU/ml), and testosterone (2.1 to 1.4 versus 2.3 to 1.7 ng/ml). Group A showed higher menstrual regularity (95% versus 87.2%) and pregnancy rates (10% versus 5.1%). Conclusions: Combination therapy of myoinositol and metformin is more effective than metformin alone in improving clinical and biochemical outcomes in infertile PCOS women.